PRODUCT MODELING OF DISCOURSE IN TEACHING WRITING IN ENGLISH - Djumaeva Guzal Azizovna (Western European Studies, 2024)
The article analyzes the concepts of the result and product of written discourse as a type of communicative activity, summarizes their differences and emphasizes the relationship. The theoretical model of the text as a product of written discourse includes general communicative properties and specific properties characterizing the content, organization and context.
Keywords: modeling; product of discourse; result of discourse; general properties of the written text